Riksinventeringen - ett instrument för m usikarkeologin - Reimers, Cbrzstiun (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2025)
The National Inventory of Historical Musical Instruments - a tool for archaeomusicology Since 1975, inventories of archaeological collections and museums in Sweden have been carried out by the National Inventory of Historical Musical Instruments (Riksinventeringen), a project of the Stockholm Music Museum. To date (1978), some 1,020 ancient and medieval musical instruments and other sound-produung devices have been registered. Seminars conducted in 1977 and 1978 and attended by Swedish and foreign musicologists and archaeologists have initiated a new discussion of the potentials of ”archaeomusicology” (cf. Cajsa Lund’s article above). Several areas have been recognised as of particular importance for methodological and problem-orientated experiments-for example the comparative study of contemporary representations, studies of the various affinities between find contexts and instrument types, and theoretical models of possible finds which facilitate interpretation of fragments while still in situ. Thus, the aims of the National Inventory are to provide scholars in various fields with as extensive a material of sources and data as possible, through card files and mimeographed reports (cf. the listing in appendix 2), and stimulate archaeomusicological research. The Inventory’s activities in this field have already aroused considerable international interest, and have led to e.g. cooperation with the Landesmuseum in Schleswig with regard to various researches, including acoustical measuring, on c. 40 early medieval German bone flutes.